Analisis Pengumpulan Al Qur’an dalam Berbagai Periode - Madaniyah, Madaniyah; Agustiar, Agustiar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to analyze the analysis of the collection of the Qur'an in various periods. This type of research is a literature study. Data collection with documentation. Data analysis with SLR. The results of the research are that analysis of the collection of the Al-Qur'an in various periods shows that the process of compiling this sacred Islamic text involved careful and systematically organized efforts. From the life of the Prophet Muhammad saw. Until the reign of Caliph Uthman bin Affan, various steps were taken to collect, verify and formalize the text of the Koran so that it remained authentic and not distorted. In the early days, collecting was done orally and in writing, with particular attention to memorization and personal notes. Then, during the time of Caliph Uthman, standardization of the Koranic text and mass reproduction were carried out to ensure uniformity and continuity. This analysis confirms that the collection of the Qur'an was a well-planned and maintained process, ensuring the continuity and authenticity of Islamic teachings